IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN MUTU LULUSAN - Sutiyono (UNISAN JURNAL, 2024)
School-Based Management is a management model that gives schools greater autonomy and encourages participatory decision-making that directly involves all school members to improve the quality of graduates in Islamic religious subjects. The results of the author's temporary observation are that SBM has been implemented since 2006 until now, seen from always carrying out SBM activities such as self-assessment self-evaluation, formulation of the school's vision, mission and goals, implementation of activities aimed at improving the quality of student learning, the existence of an evaluation and evaluation stage. activity reporting. The problem in this study is "How is the implementation of SBM in improving the quality of graduates in Islamic religious subjects at SMPIT Insan Mulia ?" School-Based Management (SBM) which is implemented is quite good. However, judging by the quality of graduates, they have not achieved satisfactory results, it can be seen from the ability of students, especially in the value of Religious Education (theory) which has decreased. This is because the infrastructure that supports the learning process is not sufficient enough because there are some facilities that are damaged or cannot be fulfilled due to limited funds and the lack of support from a small number of parents.